Sequential formation and propagation of caldera ring-faults analysed in analogue experiments - Burchardt, S.; Walter, T. R. (TRABAJOS DE GEOLOGÍA, 2009)
In a series of analogue experiments, we analysed the formation and propagation of caldera ring-faults with the Digital Image Correlation (DIC) method. The results indicate a clear sequence of faulting during subsidence and show the non-uniform propagation direction of individual faults.